Densidades de siembra y dosis de biol en la producción de pepino (Cucumis sativus l.) en Esmeraldas. - Roa Valencia, Jenny Thaice (2015)
With the objective of evaluating two siembra densities and two biol dose in the cucumber production (Cucumis sativus L.) in Emeralds, was carried out the present investigation in the "Experimental Field of the Municipal slaughterhouse of San Mateo" located in The Parish San Mateo, of the Emeralds Canton, of Emeralds County. Their Geographical location is at 79° 38' of longitude West and 0° 53' of North latitude. The duration of the experiment from the transplant until the production was of 120 days. The treatments for this investigation T1 16.666 plants/ha + 100 l of biol, T2 16.666 plants/ha + 200 l of biol, T3 13.333 plants/ha + 100 l of biol, T4 13.333 plants/ha + 200 l of biol and T5 Witness 16.666 plants without biol and they prepared at random in a Design of Complete Blocks (DBCA), with four repetitions. To determine differences among the treatments, the test of multiple ranges was used from Tukey to 0.05% of probability; an economic analysis was also made to the studied treatments. The plant in its agronomic behavior presented to the treatment T1 with the biggest plant height 1.65 m. The biggest number of fruits for plant 9.99 The biggest weight of fruit 283.10 grams and bigger yield of fruit 37879.67 kilos for hectare present it the treatment T4 (13333 plants/ha + 200 l of Biol). The biggest longitude 18.70 and diameter of fruit 5.34 cm presents it the treatment T2. The biggest utility $4.678,04 USD one has with the treatment T4 in which was used (13333 plants/ha + 200 l of Biol).